1951
DOI: 10.3181/00379727-77-18681
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Proteinuria on Localization of Radiomercury in Rat Kidney.

Abstract: LOCALIZATION OF RADIOMERCURY IN KIDNEYand the perirenal €at was indurated. There but no ,tubular degeneration. The perirenal was no evidence of sepsis.fat showed lymphocytic in,filtration and red cell extravasation. The pelves showed subacute inflammation.Conclusions. The length of survival or function of homogenous kidney transplants is not improved by the administration of ACTH or cortisone.Sections of the transplant were fixed immediately after removal. In three of the transplants microscopy showed various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1952
1952
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Further studies have shown that following administration of such compounds to humans and to animals a higher concentration of mercury is found in the kidney than in the other tissues examined, (2,3) and it appears that renal binding precedes the onset of diuresis (4,5). A number of such investigations have been carried out with the use of diuretics labelled with Hge0' (2,3), and this isotope administered as HgCl2 has been found by radioautographic means in high concentration in the renal cortex of rats (6).…”
mentioning
confidence: 99%
“…Further studies have shown that following administration of such compounds to humans and to animals a higher concentration of mercury is found in the kidney than in the other tissues examined, (2,3) and it appears that renal binding precedes the onset of diuresis (4,5). A number of such investigations have been carried out with the use of diuretics labelled with Hge0' (2,3), and this isotope administered as HgCl2 has been found by radioautographic means in high concentration in the renal cortex of rats (6).…”
mentioning
confidence: 99%
“…Schon 1949 wurde über die Kinetik des [ 203 Hg] markierten Quecksilberdiuretikums Mercuhydrin im Plasma berichtet [38]. Die Retention des [ 203 Hg]-Quecksilbersublimats (HgCl 2 ) in der Nierenrinde wurde 1951 autoradiographisch nachgewiesen [28]. Erste klinische Ergebnisse wurden 1952 mit iodhaltigen Kontrastmitteln erzielt [32].…”
Section: Historieunclassified
“…Autoradiographic technique using 203Hg has recently been applied experimentally (Lippman, Findle and Gillette 1951, Cassano et al 1969, Takahashi et al 1971, Sakai 1975). However, it can not be used in the stored paraffin sections of human autopsy materials, apart from the atomic irradiation procedure.…”
Section: Histochemicalmentioning
confidence: 99%